Argumentação jurídica nas decisões do STF em matéria tributária e o Estado de direito - Mendonça, Christine (2011)
The purpose of this doctoral thesis is to analyze the arguments presented by the Brazilian Supreme Court s decisions on tax matters so as to identify the ways in which that constitutional agency has contributed to maintain and protect the Rule of law. Theoretical tools provided by the logical-semantic constructivist method and the Luhmanian systems theory help understand the range and importance of the legal interpretation of the law, and, based on that, help verify how to process interferences coming from other social subsystems. The process of interpretation developed by the law s observer-interpreter will be registered in the juridical argumentation by him presented. And, in the case of the Supreme Court, it will be part of the reasoning supporting the Ministers votes. The analysis of those arguments is a fundamental tool to investigate the occurrence of corruption between inter-systemic codes that undermines the maintenance of the Rule of law